COMPARATIVE ANALYSIS OF FUNCTIONAL AND RADIOLOGICAL OUTCOMES BETWEEN PROXIMAL FEMORAL NAIL ANTI-ROTATION 2 AND CONVENTIONAL PROXIMAL FEMORAL NAIL AT SCHOOL OF MEDICAL SCIENCE AND RESEARCH, SHARDA UNIVERSITY GREATER NOIDA: A PROSPECTIVE OBSERVATIONAL STUDY. (Student's Journal of Health Research Africa, 2024)
IntroductionThe PFNA (Proximal Femoral Nail Antirotation) was developed to achieve improved stabilization of the femoral head and neck. The PFN (Proximal Femoral Nail) is a well-established treatment approach for proximal femoral fractures. A more recent alternative in the management of such fractures is the PFNA2 (Proximal Femoral Nail Anti-rotation 2), which incorporates a helical blade for improved bone compaction.Aim and objectivesTo evaluate the surgical and functional outcomes associated with the use of PFN and PFNA2 for the treatment of these fractures.Material and methodsFollowing ethical clearance from the Ethical Committee of Sharda University, we conducted a prospective observational study involving 50 patients who were admitted to the School of Medical Science and Research, Sharda University and Medical College Greater Noida, India.  The inclusion and exclusion criteria were applied to select eligible patients between Sept 2022 and Sept 2023.Result in the PFN group, out of the 25 study subjects 11 cases had fair modified Harris hip scores, 9 cases had good Harris hip scores, and 5 subjects had excellent modified Harris hip scores. In the PFNA2 group, out of 25 study subjects, 14 had a good modified Harris hip score, 6 had an excellent modified Harris hip score and 5 had a fair modified Harris hip score.ConclusionsPFNA2 emerges as the preferred implant choice for elderly patients with osteoporotic bone, as it offers several advantages. Its shorter operative time is particularly beneficial for patients who may have medical comorbidities, making it a marginally superior option over PFN.RecommendationA larger sample size with a longer follow-up period and a multicentric approach would have provided a more comprehensive assessment of the long-term outcomes of this clinical issue
Keywords: Proximal Femoral Nail; Proximal Femoral Nail Anti-Rotation 2; Intertrochanteric Fracture; Nail